Risk Factor of hyperemesis gravidarum incidence - Widya Nurfadillah; Rafhani Rosyidah; Evi Rinata; Yanik Purwanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Hyperemesis Gravidarum is severe and excessive nausea and vomiting, starting at 4 and 6 weeks of gestation and peaking at 8-12 weeks of pregnancy, and usually subsiding by 20 weeks of gestation. As a result of excessive nausea and vomiting, pregnant women are at risk of dehydration, vitamin and mineral deficiencies, losing 5% of body weight, and can even endanger the fetus's health. Objective: to recognize the risk factors for the incidence of hyperemesis gravidarum to detect early and reduce the consequences of hyperemesis gravidarum. Research Methods: This type of research is an analytical observational study with the research design of the Case Control method with a sample size of 240, and the ratio of cases and controls in the study is 1: 1.Results: The results showed that risk factors have an association with the incidence of hyperemesis gravidarum, namely the age of pregnant women has a value (p = 0.014 <0.05, OR = 0.38, 95% CI: 0.184-0.7998). Parity with a value of (p=0.008, OR=2.14, 95% CI: 1.253-2.656). Gestational age was (p=0.000, OR= 49.63, 95% CI: 18.730-131.51). Education with a value of (p = 0.188, OR = 0.500, 95% CI: 0.204-1.228). Maternal occupation with a value of (p=0.002, OR= 2.34, 95% CI: 1.380-3.999). Maternal pregnancy spacing with value (p=0.004, OR=2.17, 95% CI: 1.298-3.642). Non-anemic pregnant women (p=0.032<0.05, OR= 2.36, 95% CI: 1.128-4.971) and status of pregnant women with value (p=0.004, OR= 2.22, 95% CI: 1.315-3.74).Conclusion: Almost all risk factors studied had a relationship, but only maternal education in this study did not have a relationship. Maternal age, parity, gestational age, maternal employment, pregnancy distance, anemia, and BMI status are risk factors for hyperemesis gravidarum. By knowing these risk factors, it is hoped that health workers can detect early and anticipate to minimize the severity when pregnant women are exposed to HEG.